Myocardial energetics in obesity: Enhanced ATP delivery through creatine kinase with blunted stress response - Rayner, JJ; Peterzan, MA; Watson, WD; Clarke, WT; Neubauer, S; Rodgers, CT; Rider, OJ (American Heart Association, 2020)
Background: Obesity is strongly associated with exercise intolerance and the development of heart failure. Whereas myocardial energetics and diastolic function are impaired in obesity, systolic function is usually preserved. This suggests that the rate of ATP delivery is maintained, but this has never been explored in human obesity. We hypothesized that ATP transfer rate through creatine kinase (CK) (kfCKrest) would be increased, compensating for depleted energy stores (phosphocreatine/ATP), but potentially limiting greater ATP delivery during increased workload. We hypothesized that these changes would normalize with weight loss.